Hurricanes, Flood Risk and the Economic Adaptation of Businesses - Agustín Indaco; Francesc Ortega; Süleyman Taspinar (Institute of Labor Economics (IZA), 2019)
This paper argues that increases in perceived flood risk entail a negative and persistent shock to local economic activity. Our analysis is based on a rich administrative dataset that contains all business establishments in New York City around the time of hurricane Sandy. Our data also identifies exactly which buildings suffered flooding-related damage due to the hurricane. We find evidence of a persistent reduction in the employment and wage income of establishments that suffered damage, along with higher exit rates. The persistence of the effects is consistent with an upward revision of flood-risk beliefs triggered by the hurricane. These findings suggest that businesses are adapting to the higher flood-risk environment by shifting operations toward safer areas. This adjustment process may mitigate the city-wide costs associated to sea-level rise.
Keywords: H56; K42; R33; 330; climate change; sea-level rise; economic adaptation; hurricane sandy